Bolesne ślady przeszłości. Pamięć a/i trauma w kontekście wybranych narracji autobiograficznych Grażyny Jagielskiej - Ficek, Ewa (Stylistyka, 2020)
Assuming a close connection between memory, style and trauma, the author has focused on auto-description of personal experiences, retrospective thoughts, etc. referring to the difficult/traumatic experiences of an individual present in Grażyna Jagielska’s books (cf. the following titles: Miłość z kamienia. Życie z korespondentem wojennym, Kraków 2013; Anioły jedzą trzy razy dziennie. 147 dni w psychiatryku, Kraków 2014; Ona wraca na dobre. Podróż terapeutyczna, Kraków 2015). The actual analyses of the source material were preceded by an approximation of the genealogy of the trauma, its definition or possible representations, as well as by the discussion of the scientific (including humanistic) evolutions of the interest in critical incidents or their consequences. Moreover, an important point of the considerations was also the question concerning the possibility of a linguistic/discursive approach to the subject issues. As follows from the analytical part of the paper, painful traces of the past are present at various levels of the reviewed (and biographically burdened) texts. The points where the categories mentioned in the sketch title meet are related to the narrative technique, style of expressionand repertoire of symbols used by Grażyna Jagielska, with selected components of the presented world, as well as with the creation of the subject (subjected to unintentional victimisation and aiming to, among other things, explain internal conflicts). Although certain therapeutic values can be assigned to memories, the researcher is of the opinion that the textual updates considered often go beyond this simplified qualification.